The Bot - Model for Financing Slovenia’s Railway Infrastructure Development - Romih, Dejan; Dajčman, Silvo; Oplotnik, Žan Jan (Ekonomika, 2008)
The development of the railway infrastructure is of essential importance for Slovenia which lies at the crossing of V. and X. trans-European transport corridors and has been recently confronting the increasing road traffic and severe environmental conditions. To successfully cope with these challenges and achieve positive multiplicative macroeconomic effects of railway infrastructure investment the government formulated the Resolution on National Program of Public Railway Infrastructure Development (ReNPPRID). The investment program, its realization being planned for the period between 2005 and 2020, was divided into two parts: (i) the development part which includes investment to upgrade and enlarge the public railway infrastructure, and (ii) the regular part referring to implementation of public service and maintenance of existing infrastructure. Since the regular part is going to be financed from the state budget, we will focus only on the financing of those infrastructure projects that are included into the development part and promise a considerable quality improvement of the railway network and transport services.